2023
DOI: 10.17162/au.v13i4.1404
|View full text |Cite
|
Sign up to set email alerts
|

Cambios en los factores asociados al ingreso a la Universidad Nacional de la Amazonía Peruana en el contexto de la postpandemia del COVID-19

Jaime Melendez Aspajo,
Luis Enrique Torres García

Abstract: Este artículo tiene como objetivo principal identificar cambios en los factores asociados al acceso a la educación superior en una región peruana considerablemente afectada por las desigualdades y por la pandemia del COVID-19, como la Amazonía. Para ello, se planteó un estudio de enfoque metodológico cuantitativo y diseño de investigación no experimental, de tipo transversal. Se compuso una base con datos de 20 097 postulaciones a la Universidad Nacional de la Amazonía Peruana (UNAP), segmentada según las post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 13 publications
(26 reference statements)
0
2
0
1
Order By: Relevance
“…The new coronavirus disease (COVID-19) has spread rapidly throughout the planet, which was declared by the World Health Organization (WHO) as a global pandemic in the face of a health crisis that to date has left 511,107,390 infections and 6,225,901 deaths. (1,2) The COVID-19 pandemic continues to affect global populations in a variety of unprecedented ways. Families and individuals that make up these social and universal units have been particularly harmed.…”
Section: Introductionmentioning
confidence: 99%
“…The new coronavirus disease (COVID-19) has spread rapidly throughout the planet, which was declared by the World Health Organization (WHO) as a global pandemic in the face of a health crisis that to date has left 511,107,390 infections and 6,225,901 deaths. (1,2) The COVID-19 pandemic continues to affect global populations in a variety of unprecedented ways. Families and individuals that make up these social and universal units have been particularly harmed.…”
Section: Introductionmentioning
confidence: 99%
“…(1,2,3) Asimismo, una revisión sistemática de 80 estudios encontró que los procedimientos médicos deficientes son habituales en los centros de atención primarios, sean públicos o privados. (4,5) De acuerdo con la Agenda para la Salud Sostenible en las Américas 2018 -2030, la calidad es una característica primordial de la salud mundial, por lo que propone como objetivo aumentar acciones destinadas a vigilar y valorar la calidad de la atención. (6,7) La Organización para la Cooperación y el Desarrollo Económicos (OECD) evidencia que la perspectiva de vida en Suecia es una de las más favorables en el mundo, esto debido a que su sistema de atención de la salud generalmente se desempeña bien al proporcionar un buen acceso a servicios de alta calidad, sin embargo, persisten los desafíos para brindar acceso equitativo de la asistencia sanitaria a las personas que viven en varias regiones.…”
Section: Introductionunclassified
“…(2) It has been observed that this novel coronavirus disease has not only tested health facilities and public health in general, but also affects the social and economic sector; that is, it affects the well-being of the general population around the planet. (3,4) Currently, noncommunicable diseases (NCDs) are increasingly prevalent and are undermining the health systems of the nations of the planet, generating a lot of mortality; responsible for 71 % (41 million) of annual deaths globally. (5) Of the NCDs, those that affect the cardiovascular system generate the largest number of deaths per year (approximately 18 million), one of them being arterial hypertension (HTN).…”
Section: Introductionmentioning
confidence: 99%